2017
DOI: 10.1063/1.4974829
|View full text |Cite
|
Sign up to set email alerts
|

Nematic-like stable glasses without equilibrium liquid crystal phases

Abstract: We report the thermal and structural properties of glasses of posaconazole, a rod-like molecule, prepared using physical vapor deposition (PVD). PVD glasses of posaconazole can show substantial molecular orientation depending upon the choice of substrate temperature, T, during deposition. Ellipsometry and IR measurements indicate that glasses prepared at T very near the glass transition temperature (T) are highly ordered. For these posaconazole glasses, the orientation order parameter is similar to that observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 53 publications
7
45
0
Order By: Relevance
“…1E. The high degree of orientational order as revealed by X-ray scattering is consistent with previous birefringence and infrared absorption data on vapor-deposited posaconazole (21). The correlation length from this broad peak, corrected for instrumental broadening, is 2.9 nm, which is equal to approximately 6 molecules arranged laterally in-plane; this small correlation length is consistent with the view that the vapor-deposited film is not a 3D crystal.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1E. The high degree of orientational order as revealed by X-ray scattering is consistent with previous birefringence and infrared absorption data on vapor-deposited posaconazole (21). The correlation length from this broad peak, corrected for instrumental broadening, is 2.9 nm, which is equal to approximately 6 molecules arranged laterally in-plane; this small correlation length is consistent with the view that the vapor-deposited film is not a 3D crystal.…”
Section: Resultssupporting
confidence: 89%
“…We infer that this highly vertical orientation of the long axis at the free surface is therefore responsible for the high degree of orientational order seen in the vapor-deposited glass. It was previously hypothesized that posaconazole may have a highly oriented surface structure similar to that observed in nematic liquid crystals (21,40); Fig. 2 confirms that hypothesis.…”
Section: Vapor-deposited Glasssupporting
confidence: 76%
See 2 more Smart Citations
“…For glasses of itraconazole, we find a strong correlation between molecular orientation and elastic anisotropy implying that deformation along the long molecular axis of itraconazole is subject to a higher modulus. It was previously shown that vapor‐deposited itraconazole glasses have kinetic stabilities equal to or exceeding a liquid‐cooled glass , [ 48 ] indicating that glasses can simultaneously be mechanically anisotropic and kinetically stable.…”
Section: Discussionmentioning
confidence: 99%